2018
DOI: 10.1007/s00572-018-0856-6
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic acid improves arbuscular mycorrhizal symbiosis, and chickpea growth and yield by modulating carbohydrate metabolism under salt stress

Abstract: Salt stress is a major abiotic stress restricting plant growth and reproductive yield. Salicylic acid (SA) and arbuscular mycorrhizal (AM) symbioses play key roles in eliminating adverse effects of salt stress by modulating ion homeostasis and carbohydrate metabolism in crop plants. Sugars synthesized via carbohydrate metabolism act as osmotic adjustors and signaling molecules in activation of various defense responses against salt stress. The present study investigated the role of SA (0.5 mM) seed priming in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 106 publications
1
30
0
Order By: Relevance
“…PBG 5 (salt tolerant) and BG 256 (salt sensitive), inoculated with R. intraradices, was declined in response to the degree of salt stress. Glucose and total soluble sugar in salt tolerant PBG 5 (both with or without AMF-inoculation) were gradually increased when subjected to salt stress (Garg and Bharti, 2018). Total soluble sugars in several plants, i.e., wheat, fenugreek, and two legumes (soybean and cluster bean) grown under salt stress were found to vary in accordance to the degree of salt stress, AMF species, and the symbiotic interactions (Evelin et al, 2013;Datta and Kulkarni, 2014a;Talaat and Shawky, 2014).…”
Section: Soluble Sugar Free Proline Osmotic Potential and Their Rementioning
confidence: 93%
See 2 more Smart Citations
“…PBG 5 (salt tolerant) and BG 256 (salt sensitive), inoculated with R. intraradices, was declined in response to the degree of salt stress. Glucose and total soluble sugar in salt tolerant PBG 5 (both with or without AMF-inoculation) were gradually increased when subjected to salt stress (Garg and Bharti, 2018). Total soluble sugars in several plants, i.e., wheat, fenugreek, and two legumes (soybean and cluster bean) grown under salt stress were found to vary in accordance to the degree of salt stress, AMF species, and the symbiotic interactions (Evelin et al, 2013;Datta and Kulkarni, 2014a;Talaat and Shawky, 2014).…”
Section: Soluble Sugar Free Proline Osmotic Potential and Their Rementioning
confidence: 93%
“…In rice crop, flag leaf at booting stage is reported to be very sensitive to salt stress (Wankhade et al, 2013). In general, total soluble carbohydrates in the leaf tissues of AMFcolonized plants of trifoliate orange (Zou and Wu, 2011) and chickpea (Garg and Bharti, 2018) were upregulated. In trifoliate orange (Poncirus trifoliata), only sucrose was accumulated in the leaves of plants grown under 100 mM NaCl for 7 weeks, whereas glucose and fructose were unchanged even in the plants inoculated with GM and Glomus versiforme (Zou and TABLE 4 | Shoot height, flag leaf length, number of panicles, and panicle length in "Leum Pua" (LP) plants inoculated with AMF (GE; Glomus etunicatum, GG; G. geosporum, and GM; G. mosseae) of rice cv.…”
Section: Soluble Sugar Free Proline Osmotic Potential and Their Rementioning
confidence: 99%
See 1 more Smart Citation
“…Conversion of starch into dextrins and maltose is accompanied by a-and b-amylases, respectively. Researchers have confirmed that enhanced salt stress tolerance in MI plants is due to higher TSS accumulation (Talaat and Shawky, 2011;Liu et al, 2016;Garg and Bharti, 2018;Zhu et al, 2018). Arbuscular mycorrhizal fungi inoculation modifies leaf sucrose and proline metabolism by regulating the enzymatic activities responsible for sucrose and proline metabolism to enhance osmotic tolerance in the host plant (Wu et al, 2017).…”
Section: Conglomeration Of Osmolytes and Water Homeostasis To Abate Omentioning
confidence: 97%
“…Recent studies have confirmed that microbes can induce salt tolerance and endurance mechanisms (STEM) in plants ( Table 1) to enable growth and development under harsh stress conditions (Porcel et al, 2016;Barnawal et al, 2017;Chen et al, 2017;Sapre et al, 2018;Yasin et al, 2018;Jia et al, 2019). The various functions of STEM mediating this process can be summarized as follows: (i) conglomeration of osmolytes to abate osmotic stress (Hajiboland et al, 2010;Talaat and Shawky, 2011;Evelin and Kapoor, 2014;Elhindi et al, 2017;Wu et al, 2017;Garg and Bharti, 2018;Hashem et al, 2018); (ii) antioxidant barricading to block oxidative stress (Bharti et al, 2016;Qin et al, 2016;Chang et al, 2018;Chu et al, 2019;Ye et al, 2019); (iii) recuperating nutritional status and ionic homeostasis through P solubilization, siderophore production, nitrogen fixation, ion transporter activity, and exopolysaccharide (EPS) production (Porcel et al, 2016;Elhindi et al, 2017;Zhou et al, 2017;Chang et al, 2018); (iv) physiological modifications in the plant (Barnawal et al, 2017;Chen et al, 2017;Elhindi et al, 2017;Hashem et al, 2018;Ren et al, 2018); and (v) molecular modification of stress-responsive gene expression (Barnawal et al, 2017;Yasin et al, 2018;El-Esawi et al, 2019;Jia et al, 2019). Plant growth-promoting rhizobacteria (PGPR) have been reported to have mitigative effects on the growth of pepper (Yasin et al, 2018), wheat (Bharti et al, 2016;…”
Section: Introductionmentioning
confidence: 99%